Investigando aspectos e necessidades do ensino de ciências na escola Terezinha de Jesus - COSTA, Maria Zuleide Silva (2024)
This study sought to investigate the issues and needs of the science teaching in primary education through the analysis of conceptions and difficulties faced by teachers in this area, particularly teachers of the State School of Elementary and high school Terezinha de Jesus Ferreira Lima belonging to the city of AbaetetubaPA. Initially we tried to establish the current scenario of the science education in elementary education based on information obtained from a literature search. Although this research was addressed issues related to the science education in perspective STS (Science, Technology and Society), as well as the stage of the formation of the Science Teachers especially the city of Abaetetuba. We used as methodology qualitative analysis method, the research subjects were six Science Teachers Terezinha de Jesus Ferreira Lima, School the instrument used for data collection was a questionnaire, the same being composed of five steps, which address issues regarding conceptions about: Science, Teacher Education and Science regarding operations in the area, as well as the STS approach and suggestions for improvements to such teaching. The results indicate that there are several types of problems faced by the group investigated, ranging from flaws in the training process to difficulties related to the use of methodology, reflecting the reality of science teaching in elementary school these days. The results were discussed based on discussions and arguments obtained from the literature.